2019
DOI: 10.17163/ret.n18.2019.01
|View full text |Cite
|
Sign up to set email alerts
|

Happiness Management en la época de la Industria 4.0

Abstract: La era de la industria 4.0 se está caracterizando, por un lado, en la existencia de sistemas de gobernanza que gradualmente está erosionando el Estado de Bienestar. Y por otro, en la implementación de modelos de gestión empresariales basados en la precariedad laboral y la reducción masiva de puestos de trabajos derivados de la automatización de los procesos productivos y el uso extensivo de los robots. Todos estos factores influyen negativamente en la felicidad de los seres humanos, especialmente en ecosistema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 50 publications
1
33
0
5
Order By: Relevance
“…Given this statistical information, it is observed that a strategic direction that revolves around brand orientation generates positive synergies on organisations' corporate happiness in COVID-19. In general terms, this research coincides with our four study hypotheses and the literature review on the happiness management construct (Ravina-Ripoll et al, 2019;Silva Munar et al, 2020).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Given this statistical information, it is observed that a strategic direction that revolves around brand orientation generates positive synergies on organisations' corporate happiness in COVID-19. In general terms, this research coincides with our four study hypotheses and the literature review on the happiness management construct (Ravina-Ripoll et al, 2019;Silva Munar et al, 2020).…”
Section: Resultssupporting
confidence: 87%
“…A multicultural management model aimed at encouraging the following resources in job performance: creativity, commitment, technological innovation, internal entrepreneurship and social responsibility. In this way, organisations can cultivate the virtuous circle of corporate happiness' (Ravina-Ripoll et al, 2019).…”
Section: Happiness Managementmentioning
confidence: 99%
“…Este nuevo entorno, inmerso en la eclosión de nuevos modelos de negocio y marcado por la presencia de la Tecnología de Inteligencia, requiere que las empresas se diseñen con base en estructuras flexibles, eficientes y dinámicas (Ravina-Ripoll et al, 2019). Para conseguir esto es imprescindible que las personas que forman el equipo de las nuevas empresas de comunicación y relaciones públicas acepten con naturalidad y sin temor (Foncubierta-Rodríguez & Sánchez-Montero, 2019) el nuevo contexto de la comunicación digital.…”
Section: La Comunicación Como Herramienta De Las Empresas Al Serviciounclassified
“…Specifically, we analysed advertising directed at kids through Musically, Snapchat, YouTube, Instagram and BabyTV App. The criteria for choosing these applications and pages was basically the audience [70].…”
Section: Content Analysismentioning
confidence: 99%
“…In this sense, researchers [ 66 ] propose strategies for organizations to try to understand the use of social media and for organizations to determine how they transform their supporters into vocal promoters of their causes [ 67 ]. Some research has also shown that social marketing can go beyond awareness raising and behaviour change by mobilizing its target audience [ 68 , 69 , 70 ], as happiness and the achievement of well-being remains an identifiable goal pursued by private companies and public institutions [ 71 ], as well as advertisers, EFSA [ 59 ], WHO [ 49 ] and consumers (children and parents).…”
Section: Introductionmentioning
confidence: 99%